2020
DOI: 10.1128/aac.01899-19
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Mycobacteria to Isoniazid Is Related to Differences in KatG-Mediated Enzymatic Activation of the Drug

Abstract: Isoniazid (INH) is a cornerstone of antitubercular therapy. Mycobacterium tuberculosis complex bacteria are the only mycobacteria sensitive to clinically relevant concentrations of INH. All other mycobacteria, including M. marinum and M. avium subsp. paratuberculosis are resistant. INH requires activation by bacterial KatG to inhibit mycobacterial growth. We tested the role of the differences between M. tuberculosis KatG and that of other mycobacteria in INH sensitivity. We cloned the M. bovis katG gene into M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
18
2
1
Order By: Relevance
“…While we documented that EPT is active against both M. abscessus and M. tuberculosis in vitro, unexpectedly, we observed that EPT is more active against M. abscessus, which conflicts with the standard experience in antimycobacterial drug discovery [6,[46][47][48][49][50][51]. Our cocrystal structure and ITC data point to similarities and differences in the interaction of EPT with the respective LeuRS proteins.…”
Section: Discussioncontrasting
confidence: 80%
“…While we documented that EPT is active against both M. abscessus and M. tuberculosis in vitro, unexpectedly, we observed that EPT is more active against M. abscessus, which conflicts with the standard experience in antimycobacterial drug discovery [6,[46][47][48][49][50][51]. Our cocrystal structure and ITC data point to similarities and differences in the interaction of EPT with the respective LeuRS proteins.…”
Section: Discussioncontrasting
confidence: 80%
“…Previously, small alterations of KatG were demonstrated to influence the activation of INH, which is also the most important basis for INH resistance (24). The KatG sequence from M. tuberculosis was also shown to diverge from its orthologue in M. marinum, leading to a higher binding capacity to INH (17). In addition, we observed that differential expressions of katG could also contribute to antibiotic sensitivity differences between M. marinum and M. tuberculosis.…”
Section: Discussionmentioning
confidence: 59%
“…In several studies, the MICs of ETH and INH were observed to be among the most contrasting between M. tuberculosis and M. marinum (11,12). For the activation of INH, this could be attributed to small differences between the KatG structures of M. marinum and M. tuberculosis (17).…”
mentioning
confidence: 99%
“…While we documented that EPT is active against both M. abscessus and M. tuberculosis in vitro , unexpectedly, we observed that EPT is more active against M. abscessus , which conflicts with the standard experience in antimycobacterial drug discovery. 6,4247 Our cocrystal structure and ITC data point to similarities and differences in the interaction of EPT with the respective LeuRS proteins. Most notably, while the Kd was the same, the enthalpy was greater for the EPT interaction with LeuRS of M. abscessus .…”
Section: Discussionmentioning
confidence: 74%